2014
DOI: 10.5194/bg-11-4251-2014
|View full text |Cite
|
Sign up to set email alerts
|

Physical controls on CH<sub>4</sub> emissions from a newly flooded subtropical freshwater hydroelectric reservoir: Nam Theun 2

Abstract: Abstract. In the present study, we measured independently CH4 ebullition and diffusion in the footprint of an eddy covariance system (EC) measuring CH4 emissions in the Nam Theun 2 Reservoir, a recently impounded (2008) subtropical hydroelectric reservoir located in the Lao People's Democratic Republic (PDR), Southeast Asia. The EC fluxes were very consistent with the sum of the two terms measured independently (diffusive fluxes + ebullition = EC fluxes), indicating that the EC system picked up both diffusive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 77 publications
9
77
1
2
Order By: Relevance
“…The obtained diurnal trend is in accordance with findings of Sahlée et al (2014) and Lai et al (2012), who reported higher nighttime and lower daytime CH 4 emissions for a lake site in Sweden and an ombrotrophic bog in Canada, respectively. However, an opposing tendency was found by Deshmukh et al (2014), who reported higher daytime and lower nighttime CH 4 emissions from a newly flooded subtropical freshwater hydroelectric reservoir within the Nam Theun river valley, Laos. In contrast to diurnal trends obtained for CH 4 total and CH 4 diffusion , estimated ebullition events occurred erratically and showed neither clear seasonal nor diurnal dynamics.…”
Section: Application To An Exemplary Field Studymentioning
confidence: 95%
“…The obtained diurnal trend is in accordance with findings of Sahlée et al (2014) and Lai et al (2012), who reported higher nighttime and lower daytime CH 4 emissions for a lake site in Sweden and an ombrotrophic bog in Canada, respectively. However, an opposing tendency was found by Deshmukh et al (2014), who reported higher daytime and lower nighttime CH 4 emissions from a newly flooded subtropical freshwater hydroelectric reservoir within the Nam Theun river valley, Laos. In contrast to diurnal trends obtained for CH 4 total and CH 4 diffusion , estimated ebullition events occurred erratically and showed neither clear seasonal nor diurnal dynamics.…”
Section: Application To An Exemplary Field Studymentioning
confidence: 95%
“…1) and downstream of the Nakai Dam (NTH3-7, Fig. 1) were calculated with the thin boundary layer (TBL) equation (Liss and Slater, 1974) from the difference between the water surface CH 4 concentrations and the average CH 4 concentration in air (1.9 ppmv) obtained during eddy covariance deployments (Deshmukh et al, 2014) combined with a gas transfer velocity (k 600 ) as follows:…”
Section: Estimation Of Diffusive Fluxes From Surface Concentrationsmentioning
confidence: 99%
“…Floating chamber measurement was not possible for the accurate determination of the k 600 . On a few occasions, k 600 was calculated from floating chamber measurements (Deshmukh et al, 2014) and concomitant CH 4 water surface concentrations in the turbulent waters downstream of the powerhouse (section 1 at stations TRC1 and REG1), in the Xe Bangfai River downstream of its confluence with the artificial channel (XBF2), and in pristine rivers (XBF1, Nam On River, and Nam Noy River). The gas transfer velocity reached up to 45 cm h −1 and averaged 10.5 ± 12.1 cm h −1 (data not shown).…”
Section: Estimation Of Diffusive Fluxes From Surface Concentrationsmentioning
confidence: 99%
See 2 more Smart Citations